Managing inter-organizational collaborations : process views - Sydow, Jörg.; Berends, Hans. (Bingley : Emerald Publishing Limited, 2019)
This volume contains two Open Access chapters. Volume 64 of Research in the Sociology of Organizationstakes stock of research on processes of inter-organizational collaboration and explores new topics that call for inquiry.
How Technological Embeddedness Shapes Inter-organizational Collaboration ProcessesDeveloping Inter-organizational Trust; Technological Embeddedness and Trust: Faster Development of Trust; Technological Embeddedness and Trust: Insight and Control; Mutual Adaptation; Technological Embeddedness and Mutual Adaptation: The Diminishing Role of Assets; Technological Embeddedness and Mutual Adaptation: The Limits of Problem Resolution; Temporal Structuring; Technological Embeddedness and Rhythm of Interactions; Technological Embeddedness Shifts Managerial Attention; Suggestions for Future Research
Print version record.
Conclusion
Keywords: Interorganizational relations; Sociology: work & labour; Social Science -- Sociology -- General; Interorganizational relations; Electronic books